Apakah Kuesioner Kompetensi Sosial Emosional (Social and Emotional Competencies Questionare) Adil untuk Semua? Analisis Differential Item Functioning (DIF) SEC-Q pada Siswa SMP: Apakah Kuesioner Kompetensi Sosial Emosional (Social and Emotional Competencies Questionare) Adil untuk Semua? Analisis Differential Item Functioning (DIF) SEC-Q pada Siswa SMP - Pamungkas, Aris (Jurnal Ilmiah Penelitian Psikologi, 2025)
This study aims to address the question of whether the Social and Emotional Competencies Questionnaire (SEC-Q) functions fairly for all junior high school students without producing bias across groups. The SEC-Q was adapted into the Indonesian context in accordance with the International Test Commission (ITC) Guidelines for Test Adaptation. A total of 709 students in grades VII–IX from four schools participated as respondents. The SEC-Q consists of 25 items covering five core dimensions: self-awareness, social awareness, self-management, relationship management, and responsible decision-making. Differential Item Functioning (DIF) analysis was conducted using the Rasch Model by comparing male and female student groups. DIF detection was based on Chi-Square and Probability values. The results showed that 24 out of 25 items functioned fairly, while one item (item 7: “I easily understand why someone feels the way they do”) was detected as biased, with a higher likelihood of agreement among female students compared to male students. These findings confirm that, overall, the SEC-Q is a valid, reliable, and relatively unbiased instrument for assessing the social and emotional competencies of junior high school students. Nevertheless, further evaluation of the biased item is recommended to ensure that the instrument remains fully inclusive and fair across student groups. Keywords: Social and Emotional Competencies, SEC-Q, Differential Item Functioning, Rasch Model, Test Adaptation.